Pengaruh Intensitas, Durasi, Dan Efektivitas Membaca Buku Cetak Terhadap Kemampuan Analisis Mahasiswa Dengan Mediasi Hambatan Belajar Di Pascasarjana Telkom University - Al Husain, A. Hasan; Akbar, Moh. Deni; Putri, Idola Perdini; Dhiaulhaq, Aisyah Rahadatul Aisyah (Universitas Ibn Khaldun Bogor, 2025)
The analytical ability of postgraduate students to comprehend, evaluate, and logically express academic ideas remains a challenge amid the low culture of printed book literacy. This study aims to examine the influence of reading intensity, duration, and effectiveness on students’ analytical skills, with learning barriers as a mediating variable. A quantitative approach was employed, involving 275 postgraduate students from Telkom University. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression and the Baron & Kenny mediation model. The results show that learning effectiveness is the strongest predictor of analytical skills (β = 0.2062, p < 0.001), followed by reading duration (β = 0.1396, p = 0.003), while reading intensity was not significant. Learning barriers were found to partially mediate the relationship between duration and effectiveness with analytical skills (β = -0.1016, p = 0.036). The study highlights the importance of reflective learning strategies, time management, and psychosocial interventions to address learning barriers. In conclusion, analytical competence is shaped not merely by the quantity of learning but more significantly by the quality of engagement and students’ affective readiness in navigating academic processes.